Analysis of Students' Social Interaction During Mathematics Learning on Rational Numbers Using Vygotskian Perspectives - Andana, Divina; Theis, Roseli; Iriani, Dewi (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Students’ understanding of mathematical concepts is strongly shaped by the quality of social interaction that occurs during learning. Limited communication between teachers and students or among students can disrupt knowledge construction and weaken learning engagement. This study therefore examines (1) teacher–student social interactions in mathematics learning, (2) student–student social interactions, and (3) teachers’ strategies for adjusting the difficulty level of questions to students’ abilities. The study was conducted at SMP Negeri 7 Kota Jambi in May 2025 using a qualitative descriptive design. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing, with credibility ensured through source and technique triangulation. The results indicate that teacher–student interaction was in the excellent category. Teachers acted as More Knowledgeable Others by providing explanations, guiding questions, and scaffolding aligned with the Zone of Proximal Development. Student–student interaction was also excellent, as reflected in group discussions and the exchange of problem-solving strategies, although participation remained uneven. Teachers’ strategies in adjusting question difficulty were likewise excellent. These results affirm that social interaction-based learning grounded in Vygotskian theory supports students’ progression from actual to potential competence through collaboration and targeted instructional support.